Psihični vidik obravnave pacientk z izrezano maternico z vidika medicinske sestre - Jeglič, Rozalija (Obzornik zdravstvene nege, 2004)
Among all other tasks of a nurse in preoperative period of a patient awaiting hysterectomy, psychological preparation plays an important role. On the basis of literature survey, the theoretical part of the article explains the therapeutic relationship between nurse and patient, and the problem of body self-image of an obstetric patient as important factors. In the empirical part, data gathered by means of an anonymous inquiry applied to a random sample of 75 patients who had hysterectomy in 2002 because of a benign ailmentare presented. Research results revealed that pcyhological preparation is carried out although not in all cases. More than half of the researched patients (57 %) responded that nurses possess enough knowledge for a qualitative psychological preparation, and their work was in most cases evaluated as positive. As much as 53 % of the patients describe the time before operation as the most stressful part of hospitalization. This very factraises a new research question. Research results reveal that psychologicalpreparation is an important part of nursing care.
Keywords: ankete; ginekologija; Histerektomija; Hysterectomy; kirurško zdravljenje; Nursing; Oboperativna nega; Perioperative Nursing; psihična priprava; psihologija; Psychology; Questionnaires; Samokoncept; Self Concept; zdravstvena nega